Empowering Posyandu Cadres in Stunting Prevention - Ketut Suarayasa; Andi Nur Tiara AE; Afifah Kalebbi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction : Stunting is a condition of nutritional status based on length or height according to age with a Z-score value of less than -2 SD. Indonesia has set a target for achieving stunting incidence by 2024 at 14%. Meanwhile, the prevalence of stunting in 2022 is 21.6%, this figure is still very high from the target set by the government. Therefore, accelerated efforts to reduce stunting are urgently needed. There are various ways that can be done, one of which is utilizing the active role of posyandu cadres to work together to reduce the incidence of stunting. Objective : This research aims to determine the role of posyandu cadres in overcoming stunting incidents Method : This research was conducted in April 2024 by collecting academic journals obtained from Google Scholar related to empowering posyandu cadres and preventing stunting in Indonesia. Result : Based on the search, 13 articles were selected that met the requirements and will be discussed in this research, with a community service research design as an effort to empower posyandu cadres. Conclusion : Empowerment of posyandu cadres is carried out using various models starting from counseling, direct practice of measuring weighing equipment and the height of toddlers, making MPASI from local ingredients which has an effect on increasing the ability and skills of posyandu cadres to carry out early detection of stunting and provide early treatment for stunting. There is a need for a more systematic and orderly empowerment program for posyandu cadres to control the incidence of stunting among toddlers in Indonesia.